"Switching on" iron in clay minerals. Issue 6 (10th May 2019) - Ilgen, A. G.; Kukkadapu, R. K.; Leung, K.; Washington, R. E.
Abstract : We discovered a new mechanism explaining why iron in its oxidized form Fe(iii ) in clay minerals is reactive only in the presence of trace amounts of its reduced form—Fe(ii ). Abstract : Being the fourth most abundant element in the Earth's crust, iron (Fe) is a key player in myriad biogeochemical processes. Iron that resides in the structures of nano- to micron-scale clay mineral particles undergoes cycling between Fe(ii ) and Fe(iii ). This iron comprises a large redox-active pool in surface environments, controlling the fate and transport of nutrients and contaminants. The mechanism of electron transfer involving this iron species is poorly understood. We observe that Fe(iii ) in clay minerals does not oxidize arsenic As(iii ), unless a minor amount of Fe(ii ) is introduced into the predominantly-Fe(iii ) structure. These "activated" clay minerals are redox-active both in the presence and absence of oxygen. In the presence of oxygen, Fe(ii ) catalyzes the production of reactive oxygen species; however, the oxidation pathway in the absence of oxygen is unknown. Here we show that under oxygen-free conditions, the redox-active species in clay minerals is Fe II –O–Fe III moieties at the edge sites. We used in situ and ex situ spectroscopic methods, including X-ray absorption, Mössbauer, and diffuse reflectance spectroscopies, as well as ab initio calculations. Our ab initio calculations show that desorption of water from an Fe II –O–Fe III site in clay mineral requires less energy, compared to a fully-oxidized Fe III –O–Fe III site. We propose that this lower barrier for the desorption of water increases the apparent kinetics of redox reactions on clay mineral surfaces.